A Recombinase-Aided Amplification-Lateral Flow Dipstick Detection Technique for Early On-Site Diagnosis of Bacterial Blight Caused by Xanthomonas oryzae pv. oryzae in Rice - Yuxuan Hou; Jie Zhu; Chenglong Lu; Libo Fan; Mengqi Liang; Xiaobo Zhang; Benyi Cheng; Xia Xu; Junyi Gong (Rice Science)
Bacterial blight (BB) is a devastating worldwide rice disease caused by Xanthomonas oryzae pv. oryzae (Xoo), which is difficult to diagnose based on early symptoms. Conventional chemical control yields limited effectiveness once BB has spread. Consequently, it is imperative to develop a rapid, highly sensitive, specific, and easy-to-use detection technique for early on-site diagnosis of BB. We first developed a recombinase-aided amplification-lateral flow dipstick (RAA-LFD) technique for the on-site detection of Xoo. The optimized reaction temperature and time were 37 ºC and 20 min, indicating that the reaction system can be initiated by body temperature independently of any precision instruments. Evaluation of the RAA-LFD technique using the primers (RAAF2/R2) and probe (RAA2-nfo-probe) derived from the XooORF0080 locus exhibited high specificity and eliminated cross-reactivity with other bacterial species. The sensitivity of RAA-LFD is up to 1 pg/μL for Xoo genomic DNA and 100 CFU/mL for Xoo cells. Significantly, this technique accurately detected Xoo from both artificially inoculated and naturally infected rice leaves at the early stage of infection, directly deploying plant tissue fluid as the template without DNA extraction. These attributes make the developed RAA-LFD system a viable technique for the early diagnosis of BB in the field, providing technical support for early-warning systems and disease control.